Influence of Sugar Residue on the Cytotoxicity and Solubility of Several Aryl-indolo[2,3-a]pyrrolo[3,4-c]carbazoles and the Corresponding Maleimides - Ding, Ning; Lu, Zhichao; Zhang, Wei; Chun, Yuexing; Li, Yingxia (Asian Journal of Chemistry, 2012)
Indolo[2,3-a]carbazoles and the corresponding maleimides form two structurally related classes of compounds endowed with diverse biological activities. In the work we investigated the influence of sugar residue on the cytotoxicity and solubility of several aryl-indolo[2,3- a]pyrrolo[3,4-c]carbazoles and the corresponding maleimides. The results indicated that introduce a monosaccharide on a planar aromatic molecule to increase the solubility is not always effective, whereas the sugar moiety do have a profound impact on the mechanism of action for these types of compounds.